Biogeochemical impacts of fish farming on coastal sediments: Insights into the functional role of cable bacteria - Vasquez-Cardenas, Diana; Hidalgo-Martinez, Silvia; Hulst, Lucas; Thorleifsdottir, Thorgerdur; Helgason, Gudmundur Vidir; Eiriksson, Thorleifur; Geelhoed, Jeanine S.; Agustsson, Thorleifur; Moodley, Leon; Meysman, Filip J. R. (Frontiers in Microbiology, 2022)
Fish farming in sea cages is a growing component of the global food industry. A prominent ecosystem impact of this industry is the increase in the downward flux of organic matter, which stimulates anaerobic mineralization and sulfide production in underlying sediments. When free sulfide is released to the overlying water, this can have a toxic effect on local marine ecosystems. The microbially-mediated process of sulfide oxidation has the potential to be an important natural mitigation and prevention strategy that has not been studied in fish farm sediments. We examined the microbial community composition (DNA-based 16S rRNA gene) underneath two active fish farms on the Southwestern coast of Iceland and performed laboratory incubations of resident sediment. Field observations confirmed the strong geochemical impact of fish farming on the sediment (up to 150 m away from cages). Sulfide accumulation was evidenced under the cages congruent with a higher supply of degradable organic matter from the cages. Phylogenetically diverse microbes capable of sulfide detoxification were present in the field sediment as well as in lab incubations, including cable bacteria (Candidatus Electrothrix), which display a unique metabolism based on long-distance electron transport. Microsensor profiling revealed that the activity of cable bacteria did not exert a dominant impact on the geochemistry of fish farm sediment at the time of sampling. However, laboratory incubations that mimic the recovery process during fallowing, revealed successful enrichment of cable bacteria within weeks, with concomitant high sulfur-oxidizing activity. Overall, our results give insight into the role of microbially-mediated sulfide detoxification in aquaculture impacted sediments.